2013
DOI: 10.1007/s11695-013-1089-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nutritional Status During the First Year After Sleeve Gastrectomy and Roux-en-Y Gastric Bypass

Abstract: Sleeve gastrectomy (SG) is supposed to induce fewer nutritional deficiencies than gastric bypass (GBP). However, few studies have compared nutritional status after these two procedures, and the difference in weight loss (WL) between procedures may alter the results. Thus, our aim was to compare nutritional status after SG and GBP in subjects matched for postoperative weight. Forty-three subjects who underwent SG were matched for age, gender, and 6-month postoperative weight with 43 subjects who underwent GBP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
79
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 35 publications
11
79
2
2
Order By: Relevance
“…A prospective study conducted by Coupaye et al, 149 primarily to compare the nutritional effects of SG with those of RYGB, with 30 individuals in each group, also observed that transaminase levels were significantly lower after RYGB than after SG. This suggested that alterations in liver metabolism might affect synthesis or catabolism of some circulating lipids and proteins after RYGB.…”
Section: Sleeve Gastrectomymentioning
confidence: 98%
“…A prospective study conducted by Coupaye et al, 149 primarily to compare the nutritional effects of SG with those of RYGB, with 30 individuals in each group, also observed that transaminase levels were significantly lower after RYGB than after SG. This suggested that alterations in liver metabolism might affect synthesis or catabolism of some circulating lipids and proteins after RYGB.…”
Section: Sleeve Gastrectomymentioning
confidence: 98%
“…In addition, vitamin and mineral deficiencies are common after LRGB, and most patients require vitamin supplements for a long time (6). LSG is superior to LRYGB in terms of nutritional deficiencies that may occur in the postoperative period (10). Rapid transfer of stomach contents to the ileum after LRGB is associated with induction of incretins that increase insulin secretion and thus control of blood glucose levels (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly reported after gastrectomy [13][14][15], little is known regarding the prevalence and implications of micronutrient deficiency after esophagectomy. Whilst previous studies have focused on aspects related to micronutrient intake and absorption after esophagectomy, they do so without direct correlation to blood levels [6][7][8]16].…”
Section: Discussionmentioning
confidence: 99%